Bridging the Gap: The Effect of Using the Mother Tongue in Bangladeshi ELT Classrooms - Akter, Lamiya (IJLHE: International Journal of Language, Humanities, and Education, 2025)
This survey-based quantitative study investigates the role of the mother tongue (L1) in English language learning and its effects in English Language Teaching (ELT) classrooms at the tertiary level in Bangladesh. The research aims to explore how the use of L1 influences students’ comprehension, participation, and overall learning outcomes. A total of 80 students from the University of Global Village, University of Barishal, and Khulna University participated in the study through a structured questionnaire. Both quantitative and qualitative data (through open-ended questionnaire responses) were collected and analyzed to identify patterns and perceptions regarding L1 use. The findings reveal that a majority of students perceive the controlled use of L1 as supportive for understanding complex grammar and vocabulary, facilitating classroom interaction, and enhancing confidence. However, some participants indicated that excessive reliance on L1 might hinder English fluency. The study highlights the importance of a balanced approach or bilingual pedagogy suggesting that judicious integration of L1 can enhance learning effectiveness without compromising target language proficiency. These findings provide insights for ELT practitioners and policymakers to optimize classroom strategies that incorporate students’ mother tongue effectively.